(untitled) - Marshall, E. G.; 1925-2016.; Roberts, Doris; 1914-1998.; 1915-2004.; 1953-; Quaid, Randy; 1943-; Chase, Chevy; 1950-2009.; Hughes, John; Randolph, John (Burbank, CA, 2003)
Christmas is the perfect season for Clark Griswold and his family. Clarks a disaster waiting to happen. You have to see it to believe it. There are 25,000 lights on the Griswold rooftop. An exploding turkey. And a house full of relatives.
Keywords: Families; Drama; Films for the hearing impaired; Feature films; Christmas films; Christmas plays